ANALISIS PERENCANAAN STRUKTUR ATAS GEDUNG SOSIAL BUDAYA PADA KAWASAN ISLAMIC CENTRE KOTA PADANG PANJANG - Alfa Hendra; Ishak Ishak; Elfania Bastian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The City of Veranda of Mecca is the nickname for the City of Padang Panjang which can be interpreted as a road or gate to the City of Mecca. Along with the times, the nickname began to fade and experience a shift and even a decline in the understanding of Islam itself. Efforts to anticipate this, there is a desire to increase the religious values of the community by building an Islamic Center Area that is adequate and representative for a city scale with various supporting facilities needed, one of which is the Socio-Cultural Building in the Islamic Center Area of Padang Panjang City. The purpose of this research is to study and apply the planning aspects of high-rise buildings with reinforced concrete structures to be applied in a high-rise building construction design and to compare the dimensions and reinforcement in the planning with the results obtained from the author's analysis. At the time of doing the research the writer got some data such as column data, beams, floor slabs and other data from planners and data obtained directly by the author. In the data analysis method, the writer conducted a planning analysis and comparative evaluation of the structure of the Socio-Cultural Building in the Islamic Center area of Padang Panjang City using ETABS version 18 software. In terms of beam reinforcement, there are several significant differences. In the analysis of column calculations, in column K1 the dimensions and reinforcement become larger, column K2 has the same dimensions as the planner but the reinforcement is larger, columns K3 and K4 produce the same dimensions and reinforcement as the planning data. The calculation of the floor slab does not change, but in the calculation of the roof slab there is a difference between the thickness of the slab and the planning data. Keywords: Reinforced concrete structures, ETABS software, loading, reinforcement.